Research Trend of Rasch Model in the Development of Scientific Literacy Assessment Through Bibliometrics - Sunni*, Fajriatul Mufarriha; Dawana, Irgy Redityo; Jannah, Roudlotul; Sunarti, Titin; Madlazim, Madlazim; Wasis, Wasis; Rizki, Iqbal Ainur (Jurnal IPA & Pembelajaran IPA, 2024)
Scientific literacy is fundamental ability to facing the complexity of problem solving in this 21 st century era. The Rasch model is needed as a measurement model that can provide detailed information about the quality of the items used. Therefore, it is crucial for educators and researchers to understand trends in measurement and the development of science literacy instruments within the Rasch model. This study aims to provide an overview of research trends on the measurement and the development of scientific literacy instruments, especially in rasch model, through search for articles that have been published since 2002-2023. The data consisted of articles derived from scopus (n=182) and google scholar (n=960), which were then processed using microsoft excel and vosviewer to obtain bibliometric mapping visualization. This process involves the application of statistical methods to generate accurate mappings and focuses on international publications and national journals, utilizing scopus and google scholar databases to compare their results. The result showed that the research of rasch model in scientific literacy instruments development in recent years has increased and it has the potential to be researched in the future. The findings are expected to provide an overview for othe researchers regarding rasch model in scientific literacy instruments development including affiliation, subject area, document type, source type, language, countries, and mapping visualization of the network on rasch model research.